2023
DOI: 10.1177/00207640231177829
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal impact of war exposure on psychopathology in Syrian and Iraqi refugee youth

Abstract: Background: War and natural disasters lead to forced migration – and increased risk of adverse psychological outcomes – in approximately 1% of the global population. Though recent years have brought a greater understanding of the consequences of war exposure on mental health outcomes for refugee children, little is known about the longitudinal and developmental impact of these experiences on youth. Aims: The aim of this study was to assess the effect of direct exposure to war and/or combat on trajectories of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Most commonly, these include variations upon the following trajectories: resilience (i.e., few to no symptoms following trauma exposure), recovery (i.e., clinically relevant symptoms decreasing over time), chronic (i.e., stable, high levels of symptoms over time), and delayedonset (i.e., subclinical symptoms worsening over time to severe; Armenta et al, 2019;Galatzer-Levy et al, 2018). Distinct symptom trajectories have been documented in relation to posttraumatic stress disorder (PTSD) in particular (Armenta et al, 2019;, though similar patterns have also been observed in depression and anxiety symptoms (Armenta et al, 2019;Bachem et al, 2021;L. M.-E. Hinchey, Nashef, et al, 2023).…”
mentioning
confidence: 99%
“…Most commonly, these include variations upon the following trajectories: resilience (i.e., few to no symptoms following trauma exposure), recovery (i.e., clinically relevant symptoms decreasing over time), chronic (i.e., stable, high levels of symptoms over time), and delayedonset (i.e., subclinical symptoms worsening over time to severe; Armenta et al, 2019;Galatzer-Levy et al, 2018). Distinct symptom trajectories have been documented in relation to posttraumatic stress disorder (PTSD) in particular (Armenta et al, 2019;, though similar patterns have also been observed in depression and anxiety symptoms (Armenta et al, 2019;Bachem et al, 2021;L. M.-E. Hinchey, Nashef, et al, 2023).…”
mentioning
confidence: 99%
“…Despite the promising implications for improving risk assessment and prediction of symptomatology, these findings may not generalize to refugee youth. Developmentally, the effects of trauma may vary widely between youth and adults (De Bellis & Zisk, 2014): for instance, anxiety may be a more likely outcome for trauma-exposed refugee children than PTSD, which is common in their adult counterparts (Hinchey, Nashef, et al, 2023; Javanbakht et al, 2018). In general populations, the differential impact of trauma exposure on factors such as fear/safety learning, neurobiology, and psychopathology development for adults and youth has also been demonstrated (Grasser & Jovanovic, 2021).…”
mentioning
confidence: 99%